Early resection of ectopic bone in patients with heterotopic ossification about the hip after trauma. Issue 3 (March 2020) - Cole, Peter A.; Dugarte, Anthony J.; Talbot, Max; Routt,, Milton L. (Chip)
Highlights: Early resection of HO around the hip can be performed with little chance of symptomatic recurrence. Early excision may decrease the disability period and make resection easier due to better defined tissue planes. Early resection also avoids the cost and discomfort associated with unnecessary blood tests and serial bone scans. The results of this study suggest that a more aggressive approach could accelerate the patients' return to a productive lifestyle. Abstract: Objectives: Heterotopic ossification (HO) is a common complication in patients who have sustained high-energy trauma to the hip region. Traditionally, resection is performed after ectopic bone maturation. We hypothesized that early HO resection in patients with hip ankylosis after trauma can be performed with little chance of recurrence. Design: Retrospective clinical cohort. Setting: Level I Trauma Center Patients/participants: 14 patients with resection of HO about the hip performed by the senior author during a six-year period. Intervention: Early resection of Brooker Class III or IV HO. Main outcome measurements: The original injuries, risk factors for HO, post-traumatic clinical course including the workup for HO, times from fixation to resection, surgical approach, and complications were recorded. Records were reviewed to document pre and postoperative hip motions. Pre and post-operative x-rays and CT scans were reviewed to classify the HO and localize the ectopic mass. Results: Mean injury to resection interval was 6.8-months. Nine of 14 (64%) patients were followed for a mean of 32.9-months post-resection. Indications for resection included pain, stiffness, and evolving sciatic nerve lesions. Risk factors were male gender, brain injury, and extended iliofemoral and Kocher-Langenbeck surgical approaches. Complications included gluteal vein laceration, draining wounds, and recurrence. Mean flexion-extension arc of motion was 18° (range = 0–70°) preoperatively, 100° (range = 85–125°) intra-operatively, and 94° (range = 20–110°) at final follow-up. HO recurred in nine patients; functionally significant in one. Conclusion: Early resection of HO around the hip may be performed with little chance of symptomatic recurrence. Level of evidence: This is a Level IV retrospective case series.